Exploring Student’s Perspective on English Utilization in Flight Simulation: A Case Study - Silvya Serepina Hutabarat; Grace Winner N. F. Gulo; Ezra Natasya Yolanda Hutajulu; Muhammad Ryan; Risa Anggraini; Ashari P. Swondo (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to explore students’ pespectives on the use of English in flight simulation at SMK Manajemen Penerbangan Medan. The study used qualitative case study research methodology, collecting data through interviews. Researchers used in-depth interviews via direct messages with three students selected based on their willingness and availability to participate in this research. Researchers analyzed the data using thematic analysis, including coding, reducing unnecessary data, categorizing, and interpreting to identify key patterns and themes. The results provide insight into the attitudes, difficulties, and motivations of the students when using English in flight simulation. Students perceive English as an essential tool for effective communication in the aviation industry, demonstrating strong motivation to improve their English proficiency because of future career aspirations. Besides, the findings of this study can help English teachers create successful language learning plans for students studying aviation.